Effect of zeolite structure on light aromatics formation during upgrading of cellulose fast pyrolysis vapor. Issue 5 (October 2019) - Liu, Sheng-Nan; Cao, Jing-Pei; Zhao, Xiao-Yan; Wang, Jing-Xian; Ren, Xue-Yu; Yuan, Zong-Shuai; Guo, Zhen-Xing; Shen, Wen-Zhong; Bai, Jin; Wei, Xian-Yong
Abstract: Promising technology for the conversion of cellulose to aromatics by catalytic fast pyrolysis (CFP) was investigated using five zeolite catalysts, i.e., 5A, SAPO-34, HY, BETA and HZSM-5. The relationship between the porosity and acidity of different zeolites with product selectivity was studied. The results showed that both the acidity and pore size of the zeolite significantly affected the production of aromatics and coke, especially the bio-oil composition. The bio-oils obtained over 5A or SAPO-34 (small pore<5.5 nm) have relatively high oxygen content. The BTEXN (benzene, toluene, ethylbenzene, xylenes and naphthalene) carbon yields over weak acidic zeolites of HY and BETA are only 6.5% and 9.0%, respectively. Due to the appropriate pore size distribution and acid position, HZSM-5 gave the highest BTEXN carbon yield of 21.1%. Moreover, the coke deposited on the spent zeolites was analyzed by temperature programmed oxidation. Furthermore, three possible mechanisms that the acid sites catalyze vapor towards non-condensable gases, aromatics and coke were also studied. HZSM-5 achieved satisfactory deoxygenation and aromatic production simultaneously, made it a potential catalyst for producing light aromatics from reforming the biomass pyrolytic vapors. Graphical abstract: Image 1 Highlights: The mechanism that the acid sites catalyze vapor was revealed. The content of BTEXN was significantly enhanced by HZSM-5. The free radical reaction of catalytic reforming vapors over zeolites was promoted. Light aromatics formation during CFP of biomass depends significantly on zeolite type.